Respuesta :
(0.6x^4)(0.2x^6)
=0.6x^4*0.2x^6
=0.6*x^4*0.2*x^6
=(0.6*0.2)*(x^4*x^6)
=0.12*x^10
=0.12x^10
=0.6x^4*0.2x^6
=0.6*x^4*0.2*x^6
=(0.6*0.2)*(x^4*x^6)
=0.12*x^10
=0.12x^10
remember
[tex](ab)(cd)=(a)(b)(c)(d)[/tex]
and
[tex](x^m)(x^n)=x^{m+n}[/tex]
so
[tex](0.6x^4)(0.2x^6)=(0.6)(x^4)(0.2)(x^6)=[/tex]
[tex](0.6)(0.2)(x^4)(x^6)=[/tex]
[tex](0.12)(x^{4+6})=0.12x^{10}[/tex]
[tex](ab)(cd)=(a)(b)(c)(d)[/tex]
and
[tex](x^m)(x^n)=x^{m+n}[/tex]
so
[tex](0.6x^4)(0.2x^6)=(0.6)(x^4)(0.2)(x^6)=[/tex]
[tex](0.6)(0.2)(x^4)(x^6)=[/tex]
[tex](0.12)(x^{4+6})=0.12x^{10}[/tex]